2005
DOI: 10.1002/ana.20380
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular metabolites in the cortex and hippocampus of epileptic patients

Abstract: Interictal brain energy metabolism and glutamate-glutamine cycling are impaired in epilepsy and may contribute to seizure generation. We used the zero-flow microdialysis method to measure the extracellular levels of glutamate, glutamine, and the major energy substrates glucose and lactate in the epileptogenic and the nonepileptogenic cortex and hippocampus of 38 awake epileptic patients during the interictal period. Depth electrodes attached to microdialysis probes were used to identify the epileptogenic and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
228
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 260 publications
(247 citation statements)
references
References 57 publications
(114 reference statements)
12
228
3
4
Order By: Relevance
“…18 It was subsequently shown that interictal extracellular glutamate levels are also higher in the epileptogenic hippocampus compared to nonepileptogenic ones. 43 The increased interictal basal extracellular glutamate levels negatively correlate with hippocampal volume being significantly increased in the atrophic 43 hippocampus compared to nonatrophic ones. 71 The hippocampal volume negatively correlates with seizure frequency.…”
Section: Glutamate Glutamine Cyclingmentioning
confidence: 95%
See 2 more Smart Citations
“…18 It was subsequently shown that interictal extracellular glutamate levels are also higher in the epileptogenic hippocampus compared to nonepileptogenic ones. 43 The increased interictal basal extracellular glutamate levels negatively correlate with hippocampal volume being significantly increased in the atrophic 43 hippocampus compared to nonatrophic ones. 71 The hippocampal volume negatively correlates with seizure frequency.…”
Section: Glutamate Glutamine Cyclingmentioning
confidence: 95%
“…42 Thus, astrocytes in the sclerotic hippocampus seem to have a reduced capacity for glutamine synthesis and ammonia detoxification. Indeed, extracellular glutamine levels 43 and cellular glutamine levels 10,44 are reported reduced in the epileptogenic (sclerotic) hippocampus.…”
Section: Astrocytes Specific Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…14, 15 We utilized 1 H nuclear magnetic resonance (NMR) spectroscopy and highpressure liquid chromatography (HPLC) to obtain detailed maps of the metabolite content in cerebral cortex and hippocampal formation (HF) in pilocarpine-SE mice. To be able to determine glucose metabolism, we injected animals with [1,[2][3][4][5][6][7][8][9][10][11][12][13] C]glucose 15 minutes before microwave fixation of the head, and evaluated brain extracts using 13 C NMR spectroscopy and gas chromatography-mass spectrometry (GC-MS).…”
Section: Introductionmentioning
confidence: 99%
“…25 Elevated extracellular glutamate levels have also been reported in animal models of epilepsy and epilepsy patients alike, particularly in individuals with temporal lobe epilepsy. [26][27][28][29] EAAT2 p.Gly82Arg (subject A) substitutes a small hydrophobic and neutrally charged glycine with hydrophilic, positively charged arginine within the cytoplasmic loop joining the first pair of transmembrane domains ( Figure 1). The same substitution is reported in the Epi4K-EPGP dataset in a subject with infantile spasms 4 and two additional individuals with a severe EE, and de novo variants (EAAT2 p.Gly82Arg and p.Leu85Pro) were reported 33 during the preparation of this manuscript.…”
mentioning
confidence: 99%